Pengaruh lama fermentasi terhadap aktivitas antioksidan minuman fermentasi kombucha lengkuas merah (Alpinia purpurata) - Martina Hapsari; Windy Rizkiprilisa; Agnes Sari (Fakultas Pertanian Universitas Yudharta Pasuruan, 2021)
Fermentation is one way to increase bioactive compounds in various food products. Kombucha is a beverage product from traditional fermentation which involves fermenting sugar dissolved in tea with symbiotic culture of bacteria and yeast (SCOBY). Kombucha is usually made from a tea solution and not many use spices to make kombucha. In this study, red galangal kombucha will be made. The method used was Completely Randomized Design (CRD) with a variation of fermentation time (0, 2, 4, 6, 8 10) days. Parameters to be analyzed are pH, total phenol, and antioxidant activity. The results obtained are that the length of fermentation affects pH, total phenolic and antioxidant activity of red galangal kombucha drink. The pH of the red galangal kombucha drink decreased along with the length of fermentation. The most optimal total phenolic and antioxidant activity obtained at 8 days of fermentation were 854.64±0.07 gGAE/ml and 89.75±0.06%.